Understanding and prescribing plyometrics for endurance runners: A review - Wynne, K. (Strength and Conditioning Journal, 2026)
Plyometrics are an increasingly popular method of training for athletes that have been well-documented in the literature. Despite the strong evidence-base, many endurance runners do not incorporate this style of training into their training. In addition, practical, in-depth guidelines for prescribing plyometric training in this population group are lacking. This narrative review synthesizes the background on plyometrics, with a particular focus applied to endurance running performance. The literature illustrates the significant potential of plyometric training to enhance endurance running economy and performance. Recommendations and practical advice for prescribing effective plyometric programs in this athletic population are provided. This review aimed to equip coaches, health professionals, and athletes with the requisite knowledge to effectively integrate plyometrics into their routine with the view of enhancing endurance running performance.